MENINGKATKAN KEMAMPUAN BERHITUNG PENJUMLAHAN MELALUI MEDIA PEMBELAJARAN BENDA NYATA (KONKRET) DI KELAS 1 SD - Khairunisa, Widya; Imaningtyas; Muji Utami, Nidya Chandra (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
Numeracy skills are a fundamental aspect of mathematics learning in primary schools. However, many first-grade students still struggle to understand the concept of addition, especially when it is presented in an abstract manner without the aid of concrete learning media. This highlights the need for a more contextual and easily understood learning approach. This study aims to improve students’ addition skills through the use of concrete learning media in the form of Dienes Blocks in Grade I at SDN Srengseng Sawah 12 Pagi. The method used was Classroom Action Research (CAR) following the Kemmis and McTaggart model, conducted in two cycles. The research subjects consisted of 29 students. Data collection techniques included observation, interviews, documentation, and tests. The results showed improvement in three aspects of student ability: (1) understanding of addition concepts increased from 56.67% (low) to 76.67% (good); (2) ability to solve problems rose from 65.51% (fair) to 86.20% (good); and (3) ability to explain concepts using the media improved from 70.34% (fair) to 89.65% (very good). Thus, the use of concrete media such as Dienes Blocks has proven effective in helping students grasp the concept of addition, enhance active participation, and support a more meaningful learning process.